A Pilot Study: Warm Stimulation on Guangming (GB37) to Relief Asthenopia - Huang, Tao (Evid Based Complement Alternat Med, 2015)
Infrared thermometry was performed in 15 female asthenopia patients (average ± SD: 54.88 ± 7.30 years) prior to, during, and after stimulation using electrothermal Bian-stone at the Guangming (GB37) acupoints. The results of this controlled pilot study (control points at the Yongquan (KI1) and Tianshu (ST25) points) showed significant (P ≤ 0.05) increases in eyes' temperature. At the same time, no changes were found at the control points. Furthermore, after warm stimulation on Guangming (GB37) acupoints, the clinical symptoms were getting better than the control points. The symptoms' score was decreased significantly too (P ≤ 0.05). It was demonstrated that there is some relationship between Guangming (GB37) point and eyes, and warm stimulation on Guangming (GB37) could relief uncomfortable of asthenopia.